Characterization of vacuolar processing enzyme gene family and its expression in response to Fusarium oxysporum infection in Musa acuminata colla - Wan Abdullah, Wan Muhamad Asrul Nizam (2018)
Panama disease caused by Fusarium oxysporum f. sp. cubense tropical race 4 (FocTR4) has been the major threat for global banana production. Countless mitigation approaches have been implemented to avert Foc infections previously which include utilising of chemical fungicide, improvement of cultural practices and eradication through physical measures. However, most of the attempts failed to provide a satisfactory outcome in field trials. Cultivation of resistant cultivars has been shown to be the most effective approaches in counteracting the Panama disease which could be generated via genetic modification or conventional breeding. Hence, understanding the molecular events during compatible and incompatible interaction of Foc with banana could provide valuable insight into the development of genetically modified resistant banana which is crucial for protection strategies against Panama disease. This research was undertaken to study the molecular characteristic of Musa acuminata vacuolar processing enzyme (MaVPE) – a cysteine proteinase that mediates programmed cell death during FocTR4 infection. A total of seven MaVPE genes (designated as MaVPE1 through MaVPE7) were successfully identified through systemic in silico analysis of DH-Pahang (AA group) banana genome. Phylogenetic study showed that MaVPEs could be divided into seed type or vegetative type. Quantitative real-time reverse transcription polymerase chain reaction (RT-qPCR) further revealed that most of MaVPE genes expressions were induced in susceptible M. acuminata cv. Berangan after FocTR4 infection, specifically at 1 and 2 days post inoculation (DPI). However, in resistant M. acuminata cv. Jari Buaya, MaVPEs expression remained at low level at all time points after inoculation with FocTR4. The enzymatic caspase-1 activity of MaVPE also corroborated with the gene expression analysis. Interestingly, comparative proteomic profiling analysis revealed an increase in the abundance of cysteine proteinase in inoculated susceptible M. acuminata cv. Berangan as opposed to cysteine proteinase inhibitors in resistant M. acuminata cv. Jari Buaya. Consistently, inhibition of MaVPE activity through caspase-1 inhibitor reduced vacuolar membrane disintegration and decreased lesion formation of FocTR4 infected banana root. Further functional analysis using an Arabidopsis VPE-null mutant exhibited higher tolerance to FocTR4 infections and decreased cell death incidence. Taken together, the findings suggest that VPE acts as a key molecule in modulating susceptibility response in FocTR4-infected plant. This study could be the stepping stone for the development of silenced MaVPE banana via exploitation of gene editing technology. This would be useful for the production of FocTR4-resistant banana cultivar in future.